USABILIDADE OF WEBSITES OF INSTITUTIONS OF HIGHER EDUCATION IN BRAZIL THROUGH THE COURSE OF GRADUATE STUDIES IN PHYSICAL EDUCATION AND DISCIPLINE OF FOOTBALL (Fiep Bulletin - online, 2013)
To quantify the possibility of usability of websites of institutions of higher education in Brazil through the Graduate Courses in Physical Education and Discipline of Football as well as its cargo Horária in Brazil, in the Regions North, Northeast, Central West, Southeast , South Methodology: Quantify all courses for graduation in Fitness cataloged in the Database of the National Institute of Educational Studies and Research Anísio Teixeira of the Ministry of Education, through the World Computer Network and access to data available on the courses of Degree in Physical Education in Higher Education Institutions whether Universities, Colleges and University Centers, State and Private, in the statistical treatment, used to Frequency Absolute, the percentile, Fashion, the amplitude. Results: Graduate Courses in Physical Education are 762, while 464 courses ofertam the Graduate and 139 courses ofertam the Bachelor and 159 courses ofertam the Bachelor and Master; 762 of these courses exist in Brazil, only 254, or 33.3% ofertam the Discipline of Football, with load Horária found by the Fashion being of 60h, 18h with an amplitude of the 120h. Discussion: Usability is an addition to a product and can be used by user to achieve goals with effectiveness, efficiency and satisfaction and data from Table 2, have shown no such possibility of usability as regards courses of Universities in Physical Education through Discipline of Football; access to institutions of higher education must take this principle into their websites through their courses of graduation; Corroborando, there are courses in Physical Education Graduate Teachers and forming of Physical Education Professionals who work in Sports and Health See table 1, but with respect to the cultural aspect, the Football is part of daily life of Brazilians, more precisely, his soul.
Keywords: Websites; Physical Education; Football.